Engel Elasticities Derived from Lorenz and Concentration Curves: Case of Latvia - Balode, Ilze (Lithuanian Journal of Statistics, 2011)
Using information from a household budget survey of the Central Statistical Bureau of Latvia and with thehelp of the estimation of Lorenz curves of total consumption expenditure and consumption expenditure concentration curvesof separate groups of goods, Engel elasticities, concentration indices, overall elasticity indices of twelve aggregated groups ofgoods are estimated. The results obtained are new and could be meaningfully interpreted in order to explain household behaviour.